2009
DOI: 10.1080/13803390802360534
|View full text |Cite
|
Sign up to set email alerts
|

Decoding emotional prosody in Parkinson's disease and its potential neuropsychological basis

Abstract: Parkinson's disease patients may have difficulty decoding prosodic emotion cues. These data suggest that the basal ganglia are involved, but may reflect dorsolateral prefrontal cortex dysfunction. An auditory emotional n-back task and cognitive n-back task were administered to 33 patients and 33 older adult controls, as were an auditory emotional Stroop task and cognitive Stroop task. No deficit was observed on the emotion decoding tasks; this did not alter with increased frontal lobe load. However, on the cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Accordingly, other studies have also found that in PD executive function correlates with the recognition of emotional prosody (e.g., Breitenstein, Lancker, Daum, & Waters, 2001;Pell & Leonard, 2003). Furthermore, it has been suggested that some subgroups of patients show normal processing of prosody because the impairment is detected only when the executive and working memory impairments are prominent (Benke et al, 1998;Caekebeke et al, 1991;Garrido-Vásquez et al, 2012;Mitchell & Bouças, 2009). It might be Dissociating emotions in music and speech in PD 27 that basal ganglia pathways are chiefly involved in later stages of emotion recognition in prosody, where executive processes are preponderant.…”
Section: Pd and Emotion Recognition In Speech Prosodymentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, other studies have also found that in PD executive function correlates with the recognition of emotional prosody (e.g., Breitenstein, Lancker, Daum, & Waters, 2001;Pell & Leonard, 2003). Furthermore, it has been suggested that some subgroups of patients show normal processing of prosody because the impairment is detected only when the executive and working memory impairments are prominent (Benke et al, 1998;Caekebeke et al, 1991;Garrido-Vásquez et al, 2012;Mitchell & Bouças, 2009). It might be Dissociating emotions in music and speech in PD 27 that basal ganglia pathways are chiefly involved in later stages of emotion recognition in prosody, where executive processes are preponderant.…”
Section: Pd and Emotion Recognition In Speech Prosodymentioning
confidence: 99%
“…Some prior studies found more pronounced defects (e.g., Dara et al, 2008;Gray & Tickle-Degnen, 2010;Paulmann & Pell, 2010;Pell & Leonard, 2003;Yip et al, 2003), but others found no defects at all (Caekebeke, JennekensSchinkel, Linden, Buruma, & Roos, 1991;Garrido-Vásquez et al, 2012;Kan, Kawamura, Hasegawa, Mochizuki, & Nakamura, 2002;Mitchell & Bouças, 2009). Therefore, our study adds to the point that the severity of prosodic impairments is highly variable across PD samples (Gray & Tickle-Degnen, 2010).…”
Section: Pd and Emotion Recognition In Speech Prosodymentioning
confidence: 99%
See 2 more Smart Citations
“…pitch) abilities contribute to prosodic processing more generally, it also offers a more general proof-of-concept for a new approach to the cognitive neuroscience of neuropsychiatric illnesses.Illnesses like schizophrenia are increasingly appreciated as being heterogeneous innature,and abnormal behavior such as prosody perception may be impaired in some individuals, but not in others. Additionally, many of the socio-cognitive markers such as impaired prosody perception that present in schizophrenia are not specific to the illness, and alsopresent in other disorders such as autism, Alzheimer"s disease, bipolar disorder, and Parkinson"s disease (42)(43)(44)(45)(46). From a neuroscience perspective, the ability to perceive social intent through prosody is a highly complex event involvingmany cortical and subcortical brain regions (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%